Metasilicate-based alkaline mineral water improves the growth performance of weaned piglets by maintaining gut-liver axis homeostasis through microbiota-mediated secondary bile acid pathway - Jian Chen; Kanwar K. Malhi; Xiaowei Li; Xiangwen Xu; Jianxun Kang; Bichen Zhao; Yaru Xu; Xuenan Li; Jinlong Li (Animal Nutrition)
Weaning stress causes substantial economic loss in the swine industry. Moreover, weaning-induced intestinal barrier damage and dysfunction of the gut-liver axis are associated with reduced growth performance in piglets. Metasilicate-based alkaline mineral water (AMW) has shown potential therapeutic effects on gastrointestinal disorders; however, the mechanisms involved and their overall effects on the gut-liver axis have not been explored. Here, sodium metasilicate (SMS) was used to prepare metasilicate-based AMW (basal water + 500 mg/L SMS). A total of 240 newly weaned piglets were allocated to the Control and SMS groups (6 replicate pens per group and 20 piglets per pen) for a 15-day trial period. Histopathological evaluations were conducted using hematoxylin and eosin staining. To analyze the composition of the gut microbiota, 16S rRNA PacBio SMRT Gene Full-Length Sequencing was performed. Western blotting and immunofluorescence were employed to assess protein expression levels. Our results indicated that metasilicate-based AMW effectively alleviated weaning-induced colonic or liver morphological injury and inflammatory response, as well as liver cholesterol metabolism disorders. Further analysis showed that metasilicate-based AMW promoted deoxycholic acid (DCA) biosynthesis by increasing the abundance of Lactobacillus_delbrueckii in the colon (P < 0.001). This consequently improved weaning-induced colon and liver injury and dysfunction through the DCA-secondary bile acid (SBA) receptors (SBAR)-nuclear factor-kappaB (NF-κB)/NOD-like receptor family pyrin domain-containing 3 (NLRP3) pathways. Growth performance parameters, including final body weight (P = 0.034) and average daily gain (P < 0.001), in the SMS group were significantly higher than those in the Control group. Therefore, metasilicate-based AMW maintains gut-liver axis homeostasis by regulating the microbiota-mediated SBA-SBAR pathway in piglets under weaning stress. Our research provides a new strategy for mitigating stress-induced gut-liver axis dysfunction in weaned piglets.